Epidemiological profile of dental occlusion in children attending school in Envigado, Colombia (2023)
Objectives Ideal occlusion is a hypothetical standard based on teeth's morphological relationships and is characterised by perfection in anatomy and dental position, mesiodistal contacts, arch alignment and dental interdigitation. This investigation was aimed at determining the epidemiological profile of dental occlusion of children attending urban and rural public schools in Envigado during the first semester, 2010. Materials and Methods A cross-sectional, prospective, descriptive epidemiological study was carried out on patients ranging from 5 to 12 years of age. A sample size of 436 students from 6 rural schools 6 urban institutions was calculated. The oral cavity was clinically examined and different occlusal variables on the three planes of space were evaluated: sagittal, transversal, and vertical. Results 436 subjects were evaluated; average age was 8 years (±1.9). The most prevalent malocclusion for permanent dentition was Angle's Class I (49.7%, 176/354), followed by Angle's Class II (43.5%, 154/354) and Angle's Class III (6.8%, 24/354). Conclusion Angle's Class I malocclusion was the most prevalent condition with alterations in both vertical and transversal planes and space problems in the anterior segment.